Creating a classroom tiriti with young learners: A pathway to understanding te Tiriti o Waitangi - Kerry Bradshaw; Travis Pike; Sarah Ruawai; Angelique Reweti (New Zealand Journal of Teachers' Work)
This is a reflection on Riverdale Primary School’s approach to teaching Te Tiriti o Waitangi using a student-centred, inquiry-based framework. Over a 10-week inquiry in the Pae Ake classroom (Year 2 & 3), students explored Te Tiriti o Waitangi not only as a historical document but as a living agreement with ongoing cultural and societal significance. As part of this learning, they created their own classroom tiriti, using the experience to engage with principles of democratic processes, leadership, and to immerse themselves in learning about tikanga Māori. The project incorporated practical activities, including developing negotiation skills, learning to compromise, working collectively, clearly communicating expectations, and participating in a ceremonial signing. This approach helped students build meaningful connections with the values and cultural foundations of Te Tiriti o Waitangi, while enhancing their understanding of the diverse relationships, worldviews, and perspectives involved in its creation. By integrating lessons with interactive classroom experiences, this reflection illustrates how student-centred inquiry can foster understanding of Te Tiriti o Waitangi’s ongoing relevance, supporting bicultural learning in an Aotearoa New Zealand primary school context. Riverdale Primary provides an example of how student-centred inquiry can create inclusive and culturally responsive educational practices, fostering connections between students, their community, and the principles of Te Tiriti o Waitangi.